PENERAPAN STRATEGI PEMASARAN DIGITAL PADA TOKO NEW PELITA MOTOR DI KOTA BATAM - Lady; Antony Sentoso; Novi Aprillia; Kelly; Eddy Oktarianto; Andryanto; Kelvin Kwek (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
The New Pelita Motor Shop is an MSME business located in Batam City that sells various types of batteries, spare parts, and power window repair services. In the marketing strategy, New Pelita Motor uses the promotion of marketing through digital marketing which aims to develop a wider selling market through digital concepts, and also this concept will make it easier in the process of spending. With this, the output of the results of the implementation can be accepted by the New Pelita Motor, such as Google Business, and Linktree which makes it easier to access the shop's social media and also develops social media for the New Pelita Motor.